“I Wasn’t Gonna Quit, but by Hook or by Crook I was Gonna Find a Way Through for the Kids”: A Narrative Inquiry, of Mothers and Practitioners, Exploring the Help-seeking of Mothers’ Experiencing Child to Parent Violence - Toole-Anstey, Chye (Journal of family violence, 2024)
Purpose: Child to parent violence is a significant concern that has been researched over the last sixty years. However, little is known about the help-seeking pathways of parents experiencing child to parent violence (CPV). Barriers and enablers to disclosing CPV have been explored, and responses to address CPV have been nominally researched. The mapping of a disclosure to a choice of where to get help has not occurred. This study seeks to map help-seeking pathways of mothers and considers these pathways in regards to the relations within families and sociomaterial conditions. Method: This narrative inquiry utilizes response-based practice and Barad’s concept ‘intra-action’ to examine interviews with mothers (n = 11) who experience CPV, and practitioners (n = 19) who work with families experiencing CPV. Results: Five help-seeking pathways of mothers are found in this study. Three themes evident across the pathways are explored including: (1) help-seeking within pre-existing relationships; (2) mothers’ feelings of fear, shame and judgement entangled with help-seeking; and (3) conditions which enable and hinder help-seeking from family. Conclusions: This study finds sociomaterial conditions such as single motherhood and judgement limit help-seeking possibilities. Further, this study finds help-seeking occurs within pre-existing relationships along with the entanglement of CPV with other issues such as intimate partner violence (IPV) and homelessness. This study demonstrates the benefits of employing a response-based approach alongside ‘intra-action’ within a research and practice context.